PROTEOMIC PROFILING OF BLOOD-BASED BIOMARKERS IN THE EARLY DETECTION OF ALZHEIMERS DISEASE - Syeda Uroosa Hashmi; Fahad Farooq Lasi (Baqai Journal of Health Sciences)
Dementia is a massive public health issue affecting a large number of the population and according to an estimate, approximately 115.4 million people will be living with this neurodegenerative disorder by 2050. Such increasing numbers are alarming at an individual level and also not sustainable from an economic point of view. Dementia costs US$604 billion of the global economy and it is estimated that by 2030, as the rate of prevalence increases significantly, the cost of this disorder will also increase by 85%. Alzheimer’s disease (AD) is the mainstream of dementia, encompassing about 50-70% of the aged dementia population. AD is remarkable for the presence of a large number of cognitive deficiencies which results in notable impairment of social and occupational function. Alzheimer's disease has now become one of the most problematic and expensive health issues for society. Now AD is considered a chronic disease which progresses slowly with the consequences of various complex pathologies. AD is linked directly to the amyloid-beta peptides. The monomeric forms of Aβ aggregate to form fibrils and a variety of oligomers which later become neurotoxic. Alzheimer's disease is considered an incurable, irreversible, and progressive type of neurodegenerative disease, in which the symptoms of dementia become worse with time. It is essential to discover and validate biomarkers for the diagnosis of AD and enhance the establishment of new therapeutic strategies. Although the foundation of AD biomarkers from CSF and neuroimaging possesses a high degree of accuracy, there exist barriers to clinical prosecution. In past decades, much attention has been paid to blood-based biomarkers for AD. Thus, various proteomic tools can be utilized for the identification of biomarkers from blood which can serve not only in early diagnosis but also for the development of new therapeutics targeting AD.